Peritumoural budding in colorectal carcinoma, its associated factors and the potential as an independent histopathological parameter predictor - Yunus, Dahziela (2023)
Background: Throughout the past three decades, tumour budding has become a well-established additional prognostic factor in colorectal carcinoma as it’s known adverse effects on patients. The primary aim of this study is to evaluate peritumoural budding (PTB) in colorectal cancer and its associated factors. This evaluation may be beneficial for post-operative patient stratification simultaneously cementing the tumour budding values and its routine pathological report implementation. Methods: A cross-sectional retrospective study on surgically resected primary colorectal cancer. This study examined 162 haematoxylin and eosin-stained archived slides microscopically. PTB was evaluated and categorized into low-risk and high-risk budding. The association between PTB with its clinicopathological variables were statistically analysed by performing logistic regression models using SPSS. Results: PTB was observed in most patients (87.7%). High-risk budding was seen in 41 cases (25.3%) meanwhile low-risk budding was in 121 cases (74.7%). On univariable logistic regression, there is a significant association of high-risk tumour budding with adverse clinicopathological characteristics including abnormal CEA level, late TNM stage (III, IV), higher pN stage, lymphovascular invasion, perineural invasion, lymph node metastasis and recurrence (all variables have P-value <0.05). Multivariable logistic regression shows only abnormal CEA level, TNM stage III, perineural invasion and recurrence were retained and statistically significantly to the prediction, p < 0.05. The model is correctly classified in 79% of cases with the Hosmer Lemeshow test: 0.246. Conclusion: PTB evaluation is necessary and applicable as a prognostic histopathological parameter which is beneficial for patients in terms of efficacious follow-up and decision of postoperative adjuvant chemotherapy.